Hukum Internasional (Kajian Ontologis) - MAHENDRA PUTRA KURNIA (Jurnal Risalah Hukum, 2008)
International Law remains as a currently fast growing branch of law science. Some,however, feel doubt with its existence as an obviously intact law. An ontologicalreview really assists the author to get some evidences about International Law,especially related to the fast development of International Law, its compliance rate,and the demand of International Law subjects.Key words: hukum internasional (internasional law), kajian ontologis (ontological review), eksistensi(existency), ada (being).